Exclusive intermediation - Itay P. Fainmesser (Brown University, Department of Economics, 2014)
In this paper, we argue that an important function fulfilled by intermediaries is to facilitate trust by enabling social pressure towards the enforcement of informal agreements. To that end, we develop a new model that uses network theory to show that intermediaries who have exclusivity over a large enough number of interaction opportunities are able to exploit their position in the chains of interactions in the market to overcome incentive problems that would otherwise shut down the market. We derive conditions on the network structure under which intermediaries fulfill this function. Finally, we analyze two applications: (1) the market for short termapartment rentals; and (2) a financial market with investors and entrepreneurs. We provide additional examples suggesting that this paper uncovers an important channel through which intermediaries operate.
Keywords: 330; Networks; intermediation; long-term relationships; self-governance; community enforcement; trust; social capital; cooperation; strategic default; financial intermediation; Airbnb.com